Zakład Historii i Teorii Wychowania w Filii Akademii Świętokrzyskiej w Piotrkowie Trybunalskim oraz Piotrkowskie Koło Towarzystwa Historii Edukacji - Felchner, Andrzej (Biuletyn Historii Wychowania, 2008)
In Piotrków Trybunalski, in the academic year of 1984-1985, a 5-year Master’s Degree Studies in Pedagogics were launched. The school, over the 25-year span, has been significantly enlarged. At present, the Institute of Pedagogic Studies forms a part of the faculty of Social Sciences of the Jan Kochanowski University of Humanities and Sciences in Kielce. From the start, the history of learning, education and pedagogical thought have been taught. The current didactic and scientific activities in this subject are conducted by the Department of History and Theory of Education. The institution was successively directed by professors: Ryszard Wołoszyński, Teresa Wróblewska, Jerzy Kukulski and today by Andrzej Felchner. Additionally, in 2007, Piotrków Trybunalski Circle of the History of Education Society was established. It groups scholars from the Branch as well as the employees of other educational institutions from Piotrków Trybunalski.